The Effect of High Nicotine Dose on Maximum Anaerobic Performance and Perceived Pain in Healthy Non-Smoking Athletes: Crossover Pilot Study - Bartík, Peter; Šagát, Peter; Pyšná, Jana; Pyšný, Ladislav; Suchý, Jiří; Trubák, Zdeněk; Petrů, Dominika (International journal of environmental research and public health, 2023)
Background: In recent years, there has been intensive discussion about the positive effect of nicotine usage on enhancing sports performance. It is frequently applied through a non-burned tobacco form before physical activity. Nicotine is under the World Anti-Doping Agency (WADA) 2021 monitoring program. Therefore, study results that reveal either positive or negative effects are expected. This is the pilot study that reports the effect of 8 mg dose of nicotine on performance and perceived pain. Material and Methods: This research aimed to explore the oral intake effect of a high-nicotine dose (8 mg) on the maximum anaerobic performance and other selected physical performance parameters in healthy, well-trained adult athletes (n = 15, age 30.7 ± 3.6, BMI 25.3 ± 1.7). The cross-sectional study protocol included the oral administration of either sublingual nicotine or placebo tablets before the anaerobic load assessed by a standardized 30 s Wingate test of the lower limbs. Afterward, the Borg subjective perception of pain (CR 10) and Borg rating of perceived exertion (RPE) were evaluated. Wilcoxon signed-rank test was used for the analysis of data with a 0.05 level of significance. Results: The results revealed that oral administration of an 8 mg nicotine dose does not significantly improve any of the physical performance parameters monitored. We only reported the statistically significant positive effect in RPE (p = 0.03). Conclusion: Lower perception of pain intensity that we reported after nicotine application might be an important factor that affects performance. However, we did not report any improvement in physical performance parameters.
Keywords: Cross-Sectional Studies; high-nicotine dose; perceived exertion; Athletes; pilotní projekty; Nicotine; sportovci; Adult; Pain; percepce bolesti; anaerobióza; dospělí; Physical Exertion; nikotin; bolest; lidé; Humans; pain perception; tělesná námaha; anaerobic performance; průřezové studie; Anaerobiosis; Wingate test; Pilot Projects; Pain Perception